A guide to supervision in social work field education. - Agllias, Kylie; Bowles, Wendy; Cassano, Bettina; Collingridge, Mike; Dawood, Al; Irwin, Jude; Lukic, Milka; Maywald, Sue; McKinnon, Jenny; Noble, Carolyn; O'Sullivan, Justine; Wexler, Jane; et al. (Australian Learning and Teaching Council (ALTC), 2010)
This paper explores the theory and practice of supervising Australian social work students during their field education placement. It investigates: the nature of social work field education; standards and roles in social work programs; and phases of student supervision. The third section covers a number of educational foundations including: critical thinking; cultural diversity; theory and practice; student assessment; Indigenous perspectives; and working with difficulties. It is designed for practitioners who take on the role of supervising social work students during their field education placement.